2019
DOI: 10.1186/s12891-019-2877-5
|View full text |Cite
|
Sign up to set email alerts
|

Obstacles to returning to work with chronic pain: in-depth interviews with people who are off work due to chronic pain and employers

Abstract: Background: The global burden of chronic pain is growing with implications for both an ageing workforce and employers. Many obstacles are faced by people with chronic pain in finding employment and returning to work after a period of absence. Few studies have explored obstacles to return-to-work (RTW) from workers' and employers' perspectives. Here we explore views of both people in pain and employers about challenges to returning to work of people who are off work with chronic pain. Methods: We did individual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 33 publications
3
27
1
Order By: Relevance
“…Paradoxically, employers completing our survey advocated for early disclosure, but the workplace culture and management behaviours often prohibited this. This aligns with prior research in which people with chronic pain were hesitant to disclose for fear of negative outcomes, yet employers indicate a preference for early disclosure [ 81 ].…”
Section: Discussionsupporting
confidence: 86%
“…Paradoxically, employers completing our survey advocated for early disclosure, but the workplace culture and management behaviours often prohibited this. This aligns with prior research in which people with chronic pain were hesitant to disclose for fear of negative outcomes, yet employers indicate a preference for early disclosure [ 81 ].…”
Section: Discussionsupporting
confidence: 86%
“…Most of the previous studies on predictors of RTW among individuals with MSP have been conducted on workers in general, or only on male workers, and have focused on acute and sub-acute pain or non-specific low back pain [19][20][21][22][23][24]28]. A previous systematic review [33] aimed at summarizing prognostic factors related to RTW among people with long-term neck/ shoulder or back pain suggested that perceived health, recovery beliefs and work ability may be predictive of RTW.…”
Section: Plos Onementioning
confidence: 99%
“…Earlier research has also shown that individuals’ belief in their ability to work in the future is a predictor of RTW [ 24 , 25 ], and that increased work ability per se is an important predictor for RTW among women with pain in the neck/shoulder and/or back [ 26 ]. Furthermore, social support from work and outside work influences recovery from long-term MSP [ 27 ], which may have a significant role in RTW [ 28 ]. Several studies have reported that social support outside work, such as close relationships and supportive social environment, is associated with reduced MSP.…”
Section: Introductionmentioning
confidence: 99%
“…Prior underpinning work included a systematic review of supported employment interventions [14], a metaethnography on the perceptions of obstacles to RTW of people with chronic pain and employers [15], and indepth interviews with people off work due to chronic pain, and separately with employers, to capture additional detail about perceptions of obstacles to RTW not covered by our reviews [16]. Using University of Warwick's University/User Teaching and Research Action Partnership (UNTRAP) group (who have public patient involvement (PPI) training), we also consulted people living with chronic pain, who were unemployed, about their views on both the underpinning work and the feasibility study from point of design to completion.…”
Section: Intervention Developmentmentioning
confidence: 99%
“…Some of those not placed indicated that they came into the study with high expectations and felt let down. However, some noted still being pleased at having joined the study as they had found the work preparation session helpful and valued the opportunity to meet people in a similar situation (quotes 15,16).…”
Section: Participants' Perspectivesmentioning
confidence: 99%